A kind of dynamic software behavior trust model based on improved subjective logic. Issue 4 (1st October 2016) - Junfeng, Tian; Hongqiang, Jiao
Abstract: This paper proposed a kind of dynamic software behavior trust model, which is based on improved Jøsang's Subjective Logic. It used to build the trust model through turning Basic Rate and Uncertainty Factors into dynamic ones and Trace of Software Behavior (TSB) is introduced to describe the feature of Software Behavior (SB), so as to provide characteristic information, which supports the trustiness of Software Behavior. Finally, the sensitivity and efficiency of the model are demonstrated by simulation experiments, and the model can better adapt to the dynamic evaluation situation.